Nanovaccines in gastrointestinal cancers - Wang, YuHan; Huang, Peng; Li, Chun; Tu, ShengJin; Yang, Hua (Frontiers in Immunology, 2025)
Cancers of the gastrointestinal (GI) tract rank among the most commonly diagnosed malignancies worldwide, posing a heavy burden on public health. Therapeutic tumor vaccines have garnered significant interest due to their ability to promote tumor regression, eliminate minimal residual disease, create enduring immune memory, and minimize non-specific adverse effects. Recently, the integration of nanotechnology into cancer immunotherapy, particularly through the development of nanovaccines, represents a transformative approach to treating GI cancers. This review outlines the significant advancements in the design and application of nanovaccines, emphasizing the mechanisms by which these nanovaccines deliver tumor-specific antigens and immunostimulatory adjuvants, ensuring effective activation of immune responses. Despite the promise these innovative therapies hold, challenges remain, including efficient antigen delivery, safety concerns, and the complexities associated with regulatory compliance. This comprehensive analysis highlights the potential of nanovaccines in transforming treatment paradigms for GI cancers while underscoring the need for collaborative efforts to accelerate their clinical translation.